Obligation to Pray the Liturgy of the Hours: Canon 276 - Daly, Brendan P. (Roman Replies and CLSA Advisory Opinions 2016, 2016)
Some priests complain that the current Liturgy of the Hours has been designed for prayer in a monastery or a religious community. The monastery life is very ordered and organized in contrast to the lifestyle of a diocesan priest. Each part of the breviary has a hymn and is designed for choral celebration. The Liturgy of the Hours is not designed for praying alone, which is the reality for most diocesan priests. The evidence shows that many priests are not praying part or all of the Liturgy of the Hours; some claim that they are not obliged to pray the Liturgy of the Hours or that they are only obliged to pray morning and evening prayer. Are clerics obliged to pray the entire Liturgy of the Hours?